Initial Experiences of Extracorporeal Membrane Oxygenation for Trauma Patients at a Single Regional Trauma Center in South Korea - Ji Wool Ko; Il Hwan Park; Chun Sung Byun; Sung Woo Jang; Pil Young Jung (Journal of Trauma and Injury)
Purpose For severe lung injuries or acute respiratory distress syndrome that occurs during critical care due to trauma, extracorporeal membrane oxygenation (ECMO) may be used as a salvage treatment. This study aimed to describe the experiences at a single center with the use of ECMO in trauma patients. Methods We enrolled a total of 25 trauma patients who were treated with ECMO between January 2015 and December 2019 at a regional trauma center. We analyzed and compared patients’ characteristics between survivors and non-survivors through a medical chart review. We also compared the characteristics of patients between direct and indirect lung injury groups. Results The mean age of the 25 patients was 45.9±19.5 years, and 19 patients (76.0%) were male. The mean Injury Severity Score was 26.1±10.1. Ten patients (40.0%) had an Abbreviated Injury Scale (AIS) 3 score of 4, and six patients (24.0%) had an AIS 3 score of 5. There were 19 cases (76.6%) of direct lung injury. The mortality rate was 60.0% (n=15). Sixteen patients (64.0%) received a loading dose of heparin for the initiation of ECMO. There was no significant difference in heparin use between the survivors and non-survivors (70% in survivors vs. 60% in non-survivors, p=0.691). When comparing the direct and indirect lung injury groups, there were no significant differences in variables other than age and ECMO onset time. Conclusions If more evidence is gathered, risk factors and indications will be identified and we expect that more trauma patients will receive appropriate treatment with ECMO.